Acute Effect of Countermovement Jumping on Throwing Performance in Track and Field Athletes During Competition. - Karampatsos, Giorgos P; Korfiatis, Panagiotis G; Zaras, Nikolaos D; Georgiadis, Giorgos V; Terzis, Gerasimos D (J Strength Cond Res, 2017)
Karampatsos, GP, Korfiatis, PG, Zaras, ND, Georgiadis, GV, and Terzis, GD. Acute effect of countermovement jumping on throwing performance in track and field athletes during competition. J Strength Cond Res 32(1): 359-364, 2017-The purpose of the study was to investigate whether performing 3 consecutive countermovement jumps (CMJs) just before an attempt enhances performance in track and field throwers during competition. Twelve shot putters, 8 hammer throwers, 9 discus throwers, and 3 javelin throwers of both sexes participated in the study. They performed 3 maximal CMJs 85 ± 12 seconds before the second, fourth, and sixth attempt during 3 different official competitions of national level. Maximal strength (1 repetition maximum [1RM]) in squat and bench press was measured 1 week after the competition. Mean throwing performance was significantly higher after the CMJs intervention (2.66 ± 4.3%, range of increase 0.02-18.98%, p = 0.0001). Similarly, maximum throwing performance was significantly higher after the CMJs (2.76 ± 3.29%, range of increase 0.09-13.93%, p = 0.0009). All but 2 athletes increased their best performance after the CMJs. The percentage increase in performance was similar between sexes (male athletes 2.56 ± 3.01%; female athletes 3.06 ± 3.76%, p = 0.677), but it was higher for the "lighter throws" (discus and javelin throw: 4.66 ± 4.11%) compared with the "heavier throws" (shot and hammer throw: 1.62 ± 2.04%, p = 0.008). The percentage increase in performance was not significantly correlated with 1RM squat or bench press, anthropometric characteristics, and personal best performance. These results suggest that performing 3 CMJs approximately 1 minute before an attempt may increase track and field throwing performance during competition.
Keywords: Adult; Athletes; Athletic Performance; Exercise; Female; Humans; Male; Muscle Strength; Muscle, Skeletal; Sex Factors; Track and field; Young Adult